Creatine kinase B mediates UCP1-independent beige fat thermogenesis via the futile creatine cycle in mice - Jakub Bunk; Mina Ersin; Mohammed F. Hussain; Bozena Samborska; Maria Guerra-Martinez; Drishti Soni; Lawrence Kazak (Molecular Metabolism)
Objectives: Creatine kinase B (CKB) is the main isoenzyme driving creatine kinase (CK) activity in classical brown adipocytes. However, the specific CK isoenzyme active in beige adipocytes remains unknown. This study aimed to identify the predominant CK isoenzyme expressed and functionally active in beige adipocytes. Methods: CK activity was tracked using D3-creatine tracing in inguinal adipocytes from mice with adipocyte-specific Ckb deletion and their littermate controls, across in vivo and in vitro settings. Results: CKB was essential for CK activity in protein lysates and intact white and beige adipocytes isolated from inguinal fat and drives thermogenesis through the Futile Creatine Cycle. Conclusions: Similar to classical brown adipocytes, CKB is the key functional CK isoenzyme in white and beige adipocytes from the inguinal fat depot.